Genome-wide Characterization of the JmjC Domain-Containing Histone Demethylase Gene Family Reveals GhJMJ24 and GhJMJ49 Involving in Somatic Embryogenesis Process in Cotton - Li, Yan; Zhu, Shouhong; Yao, Jinbo; Fang, Shengtao; Li, Tengyu; Li, Bei; Wang, Xinyu; Wang, Mingyang; Wu, Lanxin; Pan, Jingwen; Feng, Xuemei; Chen, Wei; et al. (Frontiers in Molecular Biosciences, 2022)
The Jumonji C (JmjC) domain-containing protein family, an important family of histone demethylase in plants, can directly reverse histone methylation and play important roles in various growth and development processes. In the present study, 51 JmjC genes (GhJMJs) were identified by genome-wide analysis in upland cotton (Gossypium hirsutum), which can be categorized into six distinct groups by phylogenetic analysis. Extensive syntenic relationship events were found between G. hirsutum and Theobroma cacao. We have further explored the putative molecular regulatory mechanisms of the JmjC gene family in cotton. GhJMJ24 and GhJMJ49 were both preferentially expressed in embryogenic callus compared to nonembryogenic callus in cotton tissue culture, which might be regulated by transcription factors and microRNAs to some extent. Further experiments indicated that GhJMJ24 and GhJMJ49 might interact with SUVH4, SUVH6, DDM1, CMT3, and CMT1 in the nucleus, potentially in association with demethylation of H3K9me2. Taken together, our results provide a foundation for future research on the biological functions of GhJMJ genes in cotton, especially in somatic embryogenesis in cotton tissue culture, which is crucial for the regeneration of transgenic plants.